Role of Fish in Human Nutrition and Rural Livelihood - Rashmi (American Journal of Biology and Natural Sciences, 2025)
Fish play a very important role in improving human nutrition and supporting rural livelihood across many parts of the world, especially in countries like India. Fish are a rich source of high-quality animal protein, essential amino acids, omega-3 fatty acids, vitamins (A, D, B12), and minerals such as calcium, phosphorus, iodine, zinc, and iron. These nutrients help in proper body growth, brain development, healthy eyesight, and strong immunity. For many rural families, fish are one of the most affordable and accessible sources of nutritious food. Regular fish consumption helps reduce protein-energy malnutrition, anaemia, and micronutrient deficiency, which are common in rural populations. Apart from nutrition, fish also support rural livelihood. Millions of people depend on fishing, aquaculture, fish processing, and fish marketing as their primary source of income. Rural households earn money by catching fish from rivers, ponds, lakes, reservoirs, and by engaging in small-scale fish farming. Fish culture requires low investment, provides quick returns, and fits well with other rural activities such as agriculture and livestock rearing. Women in rural areas also participate in fish drying, cleaning, and selling, which adds to family income and empowers them economically. This study explains the biological, nutritional, and economic importance of fish in very simple zoological terms. It highlights how fish contribute to human health, how they support rural communities, and why sustainable fish management is necessary for long-term livelihood security.